Aliran-aliran Filsafat Pendidikan dan Implikasinya pada Pembelajaran: Tinjauan Kritis dalam Perspektif manajemen Pendidikan Islam - Bahrul Ulum; Dwika Putra; Linda Linda; Muhammad Faisal (Institut Agama Islam Syubbanul Wathon Magelang, 2026)
Studies on idealism, realism, pragmatism, and existentialism in education often remain descriptive, leaving their implications for managing learning in Islamic educational institutions insufficiently operational and difficult to evaluate. This study aims to (1) analyze the epistemological and pedagogical characteristics of the four philosophical streams, (2) examine their implications for learning management functions—planning, organizing, leading, and controlling—and (3) formulate an applicable integrative framework from the perspective of Islamic education management. The method is qualitative library research using a critical-comparative review, employing concept reduction, thematic categorization, and argumentative synthesis. The findings propose an alignment matrix of goals–process–assessment–school culture: idealism strengthens value orientation, realism emphasizes evidence and measurability, pragmatism structures meaningful learning experiences, and existentialism safeguards learners’ agency and responsibility within ethical boundaries.